2012
DOI: 10.1021/nl303920b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Cathode-Based ZnO Nanowire Hybrid Solar Cells

Abstract: Growth of semiconducting nanostructures on graphene would open up opportunities for the development of flexible optoelectronic devices, but challenges remain in preserving the structural and electrical properties of graphene during this process. We demonstrate growth of highly uniform and well-aligned ZnO nanowire arrays on graphene by modifying the graphene surface with conductive polymer interlayers. On the basis of this structure, we then demonstrate graphene cathode-based hybrid solar cells using two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
142
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 34 publications
1
142
0
Order By: Relevance
“…The Herman's order parameter S 〈 〉 , where φ is the deviation angle between the nanowire and the substrate normal, is a widely used measure of the preferential alignment [4,33,34]. As shown in Figure 3b, φ was measured from SEM micrographs of nanowire arrays taken at 45 o tilt (see SI for a detailed description of measurement method and discussion of geometric transformation).…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Herman's order parameter S 〈 〉 , where φ is the deviation angle between the nanowire and the substrate normal, is a widely used measure of the preferential alignment [4,33,34]. As shown in Figure 3b, φ was measured from SEM micrographs of nanowire arrays taken at 45 o tilt (see SI for a detailed description of measurement method and discussion of geometric transformation).…”
Section: Image Analysismentioning
confidence: 99%
“…Bulk heterojunction PV devices utilizing zinc oxide nanowire arrays have shown high performance when prepared in conjunction with a variety of active materials including P3HT [3,4], PCBM:P3HT [5,6], CdS [7,8], dye-sensitizers [9,10] and colloidal quantum dot (QD) thin films [1]. The minority carrier diffusion length in the active material of these devices lies in the nano-to micrometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Impressive progresses have been made which include using graphene as transparent conductive electrodes in solar cells and see-through resistive random access memories. [1][2][3] The ultrahigh carrier mobility characteristic has also been utilized in developing transistors and ultrafast photodetectors. 4,5 Moreover, it has been reported that in solar cell applications, graphene can serve as electrodes, carrier transport layers, and active layers of the device.…”
mentioning
confidence: 99%
“…Even so, the utilization of graphene film in perovskite SCs has been rarely explored up to now, therein graphene‐based films have been served as interlayers with success for high‐efficiency charge transfer or collecting 76, 77. Recently, Yan et al first reported the laminating stacked multilayer graphene serving as top electrode for semitransparent perovskite SC 78.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%